Implementation of the Fatherless Education Program in the Digital Era for Parents in Grinting Village, Tulangan District, Sidoarjo Regency - Dimas Ardika Miftah Farid; Mudhar Mudhar; Maghfirotul Lathifah; Nanda Jovita Nur Rahma; Shakila Aulia Putri (PT. Intelektiva Global Nusantara, 2025)
The phenomenon of fatherlessness—the absence of a father figure in child-rearing—has become an increasing social issue in the digital era. This condition not only affects children’s emotional balance but also weakens the family’s role in facing digital challenges. In response, this community service program aimed to enhance the awareness and parenting capacity of parents in Grinting Village, Tulangan District, Sidoarjo Regency through the Fatherless Education Program in the Digital Era. The implementation was carried out offline (face-to-face) from August to September 2025 through four main stages: (1) observation of fatherless phenomena in the community, (2) planning and preparation of educational materials, (3) socialization and training for parents, and (4) evaluation and program follow-up. A total of 40 participants—including parents, teachers, and women community group members—took part in the activities. The results indicated a significant improvement in participants’ knowledge, attitudes, and skills related to digital parenting. Parents became more capable of applying positive communication, supervising gadget use, and understanding the importance of the father’s presence in children’s development. Moreover, a community group called Digital Parenting Care was established as a platform for sharing and sustaining parenting practices. This program demonstrates that a participatory and contextual approach can serve as an effective strategy to strengthen family resilience and reduce the social impact of fatherlessness in the digital era.